Diagnóstico situacional turístico de la parroquia rural Garzareal del Cantón Zapotillo de la provincia de Loja - Armijos Maldonado, Virginia Elizabeth (2016)
The rural parish Garzareal Canton Zapotillo located at the southwestern end of the province of Loja, is located 261 km from the capital of the same name , the Parish are formed by an inner city parish , 12 rural districts nine villages in which around 473 families comprising 1796 inhabitants throng . The parish has an area of 189.668 km2 approximate. Occupies 15.10% of the territory of the Canton and 1.65 % of the province. According to the bioclimatic classification can classify this area as Tropical very dry. The average annual temperature in the parish is 25.8 ° C and the average annual rainfall is 647.7 mm. The parish is established between 200m.snm at the bottom, up to 500 meters above sea level on the high side. Garzareal has significant resources to be exploited for tourism sustainably. Moreover, the National University of Loja, represented by race Tourism Administration and according to their degree program believed realization of tourist diagnoses within the Province of Loja, through agreements made by an engagement letter with a five years; study constitutes the key to the development of projects and possible solutions to problems encountered in the study area base. This study is based on the realization of a tourism situational analysis which constitutes the starting point and the foundation on which all tourism planning process, which establishes and evaluates the status of a destination at a given time is based, is also the direct source of information that allows decisions about future strategies and the tool that will allow assessment of the success or failure of plans, programs and projects. The " Tourist Diagnosis of the rural parish of the canton Garzareal Zapotillo Loja province " project is an initiative developed with the aim of contributing to the progress of the aforementioned tourism sector. With the application of a survey of this parish , the problems in this sector in the development of tourism is evident , radicand is the lack of a situational analysis , therefore it has seen fit to setting achievable goals with which it 6 intends to use its resources and establish development strategies. The main objective is suggested: to identify alternative tourism development linked to Garzareal parish of the canton Zapotillo of the Province of Loja through a tourist situation assessment , to what was necessary to point out three specific objectives : to characterize the current state of tourism in the canton parish Garzareal Zapotillo with its opportunities and limitations ; determine the composition of the tourism supply and demand of the parish and design strategies for tourism development in the sector. To fulfill these objectives it was necessary to the implementation of the analytic- synthetic methods such as observation techniques consisting of a rapid survey of the place and finally the adaptation of the matrix characterization tour Ricaurte Carla Quijano was performed adjusting to the reality of Garzareal rural parish located 10km away from the regional town of Zapotillo, with a height of 200 to 560m.s.sns.m. at a temperature of 25.8 ° C parish with a lot of cultural and historical heritage , its traditions and customs. The parish has opportunities for its geographical location that give you the privilege of having a great diversity and wildlife, a variety of natural and cultural tourism resources and a population with an open mind to change with a fighting spirit to go beyond the limitations exist in the parish as inefficient infrastructure of basic services that possess little investment in tourism and acculturation that its inhabitants are suffering in their customs and traditions. Thus it was found that the parish does not have an infrastructure to provide hosting services or supplies. By the inventory records seven tourist attractions both natural and cultural described in each of the inventory records up, relative to the demand could get the profile of tourists through a survey that suggested that people know the parish, knowing that the increased demand of tourists coming to the parish are of Ecuadorian nationality, with an average age of 26-30 years with a higher level of education, in the most visited parish holiday season in the company family . Also a participatory workshop was developed using the Quick Method of Analysis and Participatory Planning ( MARPP) with those involved in the tourism sector and rural parish Garzareal this information obtained in the 7 workshop, a SWOT matrix that was designed to know the factors internal and external influencing directly and indirectly in the parish, I prioritize information to design a program proposal for tourism development projects and strategies. Due to the above it is concluded that in the parish is necessary to provide training and awareness projects properly to the interest of the people in the community and see an option on tourism for its economy; addition to the parish are recommended to use their tourism resources, engage in business room and board, training their citizens for tourist guides, courses where the customer is issued , use effective means of communication where you can publicize your potential interest . Mainly the Self-Government authorities Decentralized Garzareal taking this work as the basis for potential tourism development projects for Garzareal Parish.